Selisih Pajak, Profitabilitas, Ukuran Perusahaan dan Persistensi Laba - Yohanes Ferry Cahaya; Annathasia P Erasashanti; Azra Rifda Komala (Jurnal Manajemen dan Perbankan (JUMPA), 2022)
This study aims to determine the influence of book-tax difference, profitability, and firm size on earnings persistence. The data used in this study are LQ45 category companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This research is quantitative and used a purposive sampling method with a total sample of 24 companies. The analysis used SPSS 25 by performing the classical assumption test, multiple linear regression test, hypothesis testing, and the coefficient of determination test. The results show that probability has a positive influence on earnings persistence. In contrast, permanent and temporary differences as proxies for book-tax differences and firm size have no significant influence on earnings persistence.